Evaluation of Effective Factors on Home Delivery from Women Perspective under Health Comprehensive Services Centers of Kerman Medical Sciences University - Nasrin Tabasinezhad; Mansoureh Safizadeh; Mehri Hasanzadeh; Sirous Salari; Mahin Saber Mahani; Batool Damadi (Kerman University of Medical Sciences, 2020)
Evaluation of Effective Factors on Home Delivery from Women Perspective under Health Comprehensive Services Centers of Kerman Medical Sciences University Tabasinezhad Nasrin1, Safizadeh Mansoureh2, Hassanzadeh Mehri3, Salari Sirous2, Saber Mahani Mahin3, Damadi Batool4*   1. M.Sc. in Health Education, BSc in Health Network Management, Deputy of Health, Kerman University of Medical Sciences, Kerman, Iran 2. MD, Department of Family Health, Deputy of Health, Kerman University of Medical Sciences, Kerman, Iran 3. BSc in Public Health, BSc in Family Health, Deputy of Health, Kerman University of Medical Sciences, Kerman, Iran 4. BSc Midwifery, BSc in Family Health, Deputy of Health, Kerman University of Medical Sciences, Kerman, Iran Corresponding Author: Batool Damadi Address: Deputy of Health, Shafa Intersection, Jomhouri Blvd, Kerman, Iran  Tel: 00983431215750        Email: Bdamadi_1389@gmail.com Abstract: Background & Objectives: Maternal mortality rate due to complications of pregnancy and delivery is one of the most important indicators of the development status of countries which has a direct relationship with delivery conditions. Preposition home delivery increase, this study has been done for the purpose of study of mothers views who are under Kerman Medical Sciences University for causes detecting of delivery at home. Methods: This study was a descriptive-analytical one that was performed cross-sectionally on 503 mothers who are under comprehensive health service centers of Kerman University of Medical Sciences who were included in the study using convenience sampling method. The data were collected using a researcher-made questionnaire and were analyzed by descriptive statistics as well as logistic regression in SPSS software Results: The most causes of home delivery were the high cost of delivery at hospitals (71.4%) and family's decision (33.4%).  Unfavorable weather conditions (0.6%) had the least important role in home birth. The highest number of home births was related to non-Iranian population (98.4%). Based on the goodness of fit of logistic regression model, only the number of pregnancies and number of stillbirths had a significant effect on home birth. Conclusion: Since the high cost of delivery at hospital is the major reason preventing non-Iranian women from referring to the hospital, it is necessary to adopt new policies for admission of non-Iranian women in public hospitals and provide insurance to them so that they would be encouraged to have delivery at hospital.   Keywords: Home Birth, Effective factors, Women, Comprehensive Health Service Centers, Health Centers   Citation: Tabasinezhad N, Safizadeh M, Hassanzadeh M, Salari S, Saber Mahani M, Damadi B. Evaluation of Effective Factors on Home Delivery from Women Perspective under Health Comprehensive Services Centers of Kerman Medical Sciences University. Journal of Health Based Research 2020; 6(1): 15-24. [In Persian]